Rehabilitation in Pediatric Heart Failure and Heart Transplant - Ubeda Tikkanen, Ana; Berry, Emily; LeCount, Erin; Engstler, Katherine; Sager, Meredith; Esteso, Paul (Frontiers in Pediatrics, 2021)
Survival of pediatric patients with heart failure has improved due to medical and surgical advances over the past decades. The complexity of pediatric heart transplant patients has increased as medical and surgical management for patients with congenital heart disease continues to improve. Quality of life in patients with heart failure and transplant might be affected by the impact on functional status that heart failure, heart failure complications or treatment might have. Functional areas affected might be motor, exercise capacity, feeding, speech and/or cognition. The goal of rehabilitation is to enhance and restore functional ability and quality of life to those with physical impairments or disabilities. Some of these rehabilitation interventions such as exercise training have been extensively evaluated in adults with heart failure. Literature in the pediatric population is limited yet promising. The use of additional rehabilitation interventions geared towards specific complications experienced by patients with heart failure or heart transplant are potentially helpful. The use of individualized multidisciplinary rehabilitation program that includes medical management, rehabilitation equipment and the use of physical, occupational, speech and feeding therapies can help improve the quality of life of patients with heart failure and transplant.